Company commander - MacDonald, Charles Brown 1922- (Burford Books, 1999)
As a newly commisioned Captain of a veteran Army regiment, MacDonald's first combat was war at its most hellish-the Battle of the Bulge. In this plain-spoken but eloquent narrative, we live each minute at MacDonald's side, sharing in all of combat's misery, terror, and drama. How this green commander gains his men's loyalty in the snows of war-torn Europe is one of the great, true, unforgettable war stories of all time.